Implementation of Bureaucratic Reform: A Case Study From The Indonesian Armed Forces And Its Challenges - Ramadhan, Kiki Rezki; Iqbal, Nur Muhammad; Eris, Wilda Shaliha; Leksmanawati, Widya (Technium Social Sciences Journal, 2022)
The Indonesian National Armed Forces (TNI) is a state instrument whose primary duty is in the field of defense to safeguard Indonesian sovereignty. The history of the TNI’s involvement in guarding the long journey of the Indonesian nation began even before Indonesia’s independence when it was still carried out in the form of a people’s resistance body and was regional. During the New Order era, the TNI, which had received special rights known as the Dual Function of ABRI, was finally abolished in 1998 along with the resignation of the late President Suharto after 32 years in power. After the reform, the TNI has consolidated and left behind the dual role of the past which for many people is more likely to be seen as a tool to maintain the centralized power of the country’s leaders. After more than two decades of reforming the TNI, it has now made the TNI one of the largest military forces in the Asean region and even reckoned with by the world. Likewise, the return of public trust in the TNI can be seen through various studies conducted by survey institutions with the results that almost always place the TNI in the first place. However, in contradiction with all the results that have been achieved, the value of the implementation of bureaucratic reform in TNI institutions is only able to penetrate the category of good enough, so this article is made as an initiation with a focus on seeing implementation, challenges to what factors influence bureaucratic reform within the Indonesian National Armed Forces.